An unusual case of renal tubular acidosis. (4th April 2011) - Carr, F; Prasad, B
Abstract : A 40-year-old female with a history of glue sniffing and intravenous drug use presented to hospital with a week's history of feeling generally unwell. She had had multiple admissions to hospital with similar presentations in the past. On examination, the only significant clinical finding was that of a reduced level of consciousness. Laboratory investigations revealed a hyperchloremic normal anion gap metabolic acidosis with a positive urine anion gap and a urine pH of 6.5 combined with a severely low hypokalaemia. She was subsequently diagnosed with renal tubular acidosis type 1, secondary to toluene exposure from glue sniffing and was treated with intravenous fluids and potassium replacement and discharged home with oral potassium citrate and advised to stop her inhalant use.